ANALYSIS OF FACTORS ASSOCIATED WITH SMOKING BEHAVIOR IN ADOLESCENTS IN BLANG MANGAT DISTRICT KOTA LHOKSEUMAWE - Suryawati, Ida; Gani, Abdul; Mariyati, Mariyati (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2022)
Background: Smoking behavior is the biggest health problem that can cause death. Tobacco use at an early age can form a lifelong smoker and stunt the growth of children. The prevalence of smoking among adolescents in Indonesia tends to increase every year which is induced by many factors. The aim of this study is to analyze the factors associated with smoking behavior in adolescents in KecamatanBlang Mangat, Lhokseumawe. Method: This analytic study using cross-sectional approach. The population in this study were all male students in four public Junior High School with a total of 584 students. The number of samplein this study were 327 respondents. The sampling technique employed is Quota random sampling. The number of respondents for each school is determined based on the total population of each school. Data collection was performed using questionnaires which thereafter analysed utilizing multivariate test. Result: The results show that there is a correlation between knowledge and smoking behavior (p=0.000); the correlation between adolescent perception and smoking behavior (p=0.001); the correlation between family support and smoking behavior (p=0.000); the correlation between peer influence and smoking behavior (p=0.000); the correlation between stress and smoking behavior (p=0.000). Family support is the most dominant factor influencing smoking behavior (p0.001). It is seen from the biggest value of exp B which is 15.355. Suggestion: Efforts that can be made to prevent smoking behavior in adolescents are by maintaining good communication, positive support from families, and controlling children's behavior.